New frontiers in mining complex patterns : 8th International Workshop, NFMCP 2019, held in Conjunction with ECML-PKDD 2019, Würzburg, Germany, September 16, 2019, Revised selected papers /: 8th International Workshop, NFMCP 2019, held in Conjunction with ECML-PKDD 2019, Würzburg, Germany, September 16, 2019, Revised selected papers. (2020) - Unknown
No abstract available